Hierarchical Multiporous Nickel for Oxygen Evolution Reaction in Alkaline Media. Issue 24 (27th November 2019) - Assavapanumat, Sunpet; Ketkaew, Marisa; Garrigue, Patrick; Lapeyre, Véronique; Reculusa, Stéphane; Wattanakit, Chularat; Kuhn, Alexander
Abstract: The front cover artwork for Issue 24/2019 is provided by researchers from the Analytical Nanosystems group of the Institute of Molecular Science in Bordeaux (France) and the Advanced Magic Porous Material group at the Vidyasirimedhi Institute of Science and Technology (Thailand). The image illustrates one of the results of a long lasting collaboration between the two groups dedicated to the design, the synthesis and applications of advanced porous materials. In this particular case, the combination of macroporous and mesoporous features in a nickel layer is tested for the electrochemical oxygen evolution reaction. See the Full Paper itself at https://doi.org/10.1002/cctc.201901509 . Abstract : " This stimulated us to use our know‐how " This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research at https://doi.org/10.1002/cctc.201901509 .